1901 Mich. Pub. Acts Sess. Laws 154, Local Acts, no. 344, tit. 7, § 24, pt. 10. - (:unkn) unknown (General Publisher, 1901)
[T]o direct the location of slaughter houses, markets and buildings for the storing of gunpowder and other combustible and explosive substances[.]
--
Keywords: GUN POWDER STORAGE